Peran Fasilitator Pendamping dalam Meningkatkan Literasi Keuangan Nasabah BTPN Syariah Pucuk - Rangga Eka Saputra; Yanda Bara Kusuma (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The role of the companion facilitator in enhancing the financial literacy of customers at BTPN Syariah Pucuk branch is crucial. This research aims to examine this role and its impact on customers' financial literacy. Using a qualitative method with a case study approach, data were collected through in-depth interviews, observations, and document analysis. The findings indicate that the companion facilitator significantly improves customers' financial knowledge and skills, aiding them in making better financial decisions.